Reconnoitering Students’ Satisfaction of an Online Based Assessment System to Improve Usability using PSO: An Examination into a Problem Solving and Programming Course - Vairamuthu, S.; Margret Anouncia, S. (Engineering, Technology & Applied Science Research, 2016)
End users’ computing environment has been consistently changing in recent years due to the major advancements of Information Technology. This work aimed to measure the level of users’ satisfaction and provide feedbacks for continuous improvement of a course offered in an academic institution. End users here were the students enrolled for the course and the faculty members who offered the same and also acted as an assessor for the assessments. All assessments were scheduled and conducted online. This study was conducted to focus on two different aspects: Measuring User satisfaction and investigating information systems measures to improve usability using nature inspired computing. For user satisfaction analysis, the study employed the Multicriteria Satisfaction Analysis. The course considered was a problem solving and programming course offered to the fresh students enrolled in the first year of the undergraduate degree program in the academic institution during 2015-2016. To identify the factors for improved usability, PSO was employed in this work.